2022
DOI: 10.1038/s41375-022-01669-z
|View full text |Cite
|
Sign up to set email alerts
|

Prospective validation of a biomarker-driven response prediction model to romiplostim in lower-risk myelodysplastic neoplasms – results of the EUROPE trial by EMSCO

Abstract: The EUROPE phase 2 trial investigated the predictive value of biomarkers on the clinical efficacy of single agent romiplostim (ROM) treatment in patients with lower-risk myelodysplastic neoplasms (LR-MDS) and thrombocytopenia within the ‘European Myelodysplastic Neoplasms Cooperative Group‘ (EMSCO) network. A total of 77 patients with LR-MDS and a median platelet count of 25/nl were included, all patients received ROM at a starting dose of 750 μg by SC injection weekly. Thirty-two patients (42%) achieved a hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Five-year followup for transformation to AML and death did not differ between the 2 groups [29]. A subsequent trial of romiplostim in LR MDS with <5% marrow blasts demonstrated a hematologic improvement-platelet response (HI-P) rate of 42% with a median response duration of 48.5 weeks [30]. Predictors of response were SRSF2 mutation status and baseline hemoglobin levels, but not endogenous TPO levels or platelet transfusion history.…”
Section: Therapeutic Optionsmentioning
confidence: 92%
“…Five-year followup for transformation to AML and death did not differ between the 2 groups [29]. A subsequent trial of romiplostim in LR MDS with <5% marrow blasts demonstrated a hematologic improvement-platelet response (HI-P) rate of 42% with a median response duration of 48.5 weeks [30]. Predictors of response were SRSF2 mutation status and baseline hemoglobin levels, but not endogenous TPO levels or platelet transfusion history.…”
Section: Therapeutic Optionsmentioning
confidence: 92%
“…9,19 Notably, in low-risk MDS, SRSF2 may predict response to romiplostim. 20 Our study is limited by the small sample size and its retrospective nature. While all patients did have pathogenic SRSF2 mutations with significant VAFs, we cannot conclude that this genetic abnormality defines CCUS-IT.…”
Section: Wementioning
confidence: 94%